Evaluation of deep learning architectures applied to identification of diseases in grape leaves - Oliveira, Flávio R. S.; Farias, Felipe C.; Caldas, Bernardo João de Barros (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2018)
Vale do São Francisco in Pernambuco is one of the most economically important poles in the state and among its cultivars, it is worth mentioning the grape culture. This sector faces challenges related to the response time between identifying a field infestation and taking corrective actions, in order to minimize losses. This work comprises a comparative analysis between deep learning architectures, applied to identification of diseases in grape cultivars. Results suggest that the use of these technologies is plausible to differentiate healthy grape leaves from leaves presenting one of three different types of diseases, obtaining near 100% accuracy in studied database using an architecture that can be employed in embedded devices.